Progress in insulated gate bipolar transistor thermal management: From fundamentals to advanced strategies - Rehman, Tauseef-ur; Park, Cheol Woo (Renewable & sustainable energy reviews, 2025)
Renewable energy and electric vehicles are crucial subjects of the global transition towards a sustainable future. Insulated gate bipolar transistors (IGBTs) are essential components of these systems, generating substantial heat during operation. This review provides a comprehensive overview of the thermal control strategies for IGBTs, covering fundamental concepts, heat generation mechanisms, thermal failure modes and state-of-the-art cooling techniques. The review emphasises the reduction of junction temperature, thermal resistance and temperature gradient in IGBT chips and modules. Various cooling technologies are explored, including air and liquid cooling with novel configurations, PCM-based cooling, two-phase cooling (microchannels, thermosyphon and vapour chambers), nanofluid-based cooling, spray and jet impingement and hybrid configurations. This review highlights the significance of flow rate, fluid type, cooling system configuration and flow type (single or two-phase) on cooling performance. Key findings from extensive research are summarised, including the inadequacy of natural air circulation for thermal buffering, the effectiveness of passive cooling techniques for low to moderate heat generation, effectiveness of two-phase cooling for elevated heat flux and the directions for making the cooling systems hybrid (active and passive). This review sums up by discussing the outlook, challenges and future directions in IGBT thermal management, emphasising the need for further investigation into the diverse areas of thermal management leading towards the implications of the research at commercial level. •Natural air cooling is inadequate for IGBTs; forced convection is crucial.•Passive cooling is suitable for low-to-moderate heat generating IGBTs.•Vapour chambers reveal superior performance amongst passive cooling systems.•Passive–air hybrid cooling system benefits high-power IGBTs with space constraints.•Two-phase microchannel heat sinks outperform air cooling.